2021
DOI: 10.2196/24527
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Text Messaging Interventions on Blood Pressure Control Among Patients With Hypertension: Systematic Review of Randomized Controlled Trials

Abstract: Background Controlling blood pressure (BP) is an international health concern, and high BP is a major contributor to cardiovascular disease mortality. Evidence has shown that educational interventions directed at patients potentially improve BP control and adherence to medications and lifestyle modifications. In addition, a text messaging intervention has a potential effect on BP control; however, the dosage of a text messaging intervention has not been determined in previous reviews, resulting in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 57 publications
1
12
0
1
Order By: Relevance
“…In the recent decade, hypertension is widely recognized to sharply increase the incidence of cardiovascular disease, which has dramatically increased the medical expenditure for patients around the world (44,45). Through many in vitro and in vivo experiments, we now know that long-term effective antihypertensive therapy can avert hypertension-related mortality by nearly 50% (46).…”
Section: Effects On Blood Pressurementioning
confidence: 99%
“…In the recent decade, hypertension is widely recognized to sharply increase the incidence of cardiovascular disease, which has dramatically increased the medical expenditure for patients around the world (44,45). Through many in vitro and in vivo experiments, we now know that long-term effective antihypertensive therapy can avert hypertension-related mortality by nearly 50% (46).…”
Section: Effects On Blood Pressurementioning
confidence: 99%
“…Previous intervention studies have demonstrated the efficacy of text messaging and brief educational encounters about hypertension in helping participants to control blood pressure and improve medication adherence, 27-29 including one which showed that the text messaging intervention halved the odds of participants with hypertension having uncontrolled blood pressure after six months; 28 however, we could not find any previous RCT that included people with IDD. We conducted a RCT to assess the impact of a low-cost education and reminder system related to anti-hypertensive medication and lifestyle on the outcomes of CVD-related ED visits and IP stays.…”
Section: Purposementioning
confidence: 83%
“…With the rapid increase in smartphone ownership, 67 Tai Chi practice could be integrated with smartphone use, allowing regular delivery of reminders to patients with hypertension. 68 These reminders can be in the form of text, voice, image, or video to help patients establish and maintain a regular Tai Chi exercise routine.…”
Section: Discussionmentioning
confidence: 99%